Literatur Review: Analysis of Adverse Effect Profiles Across Antihypertensive Classes and Their Implications for Patient Therapeutic Adherence - NETI AFRIYANI; Herlin Sulita; Ariesa Oktamauri (Perkumpulan Dosen Muda Bengkulu, 2026)
Background: Hypertension continues to pose a formidable challenge to global public health, heavily contributing to the burden of cardiovascular disease, serving as a primary driver of cardiovascular-related morbidity and mortality. While antihypertensive medications are essential for blood pressure management, the diverse pharmacological classes involved are associated with various side effects. These adverse reactions can diminish patient comfort and subsequently undermine long-term treatment adherence. Purpose: The primary objective of this literature review was to assess the distinct adverse effect profiles of various antihypertensive drug categories and to investigate how these reactions specifically influence patient compliance. Methods: A comprehensive electronic search was executed using PubMed and Google Scholar databases, utilizing targeted keywords associated with hypertension and its diverse pharmacological agents. The selection process targeted English and Indonesian studies published from 2015 to 2025 that centered on patients diagnosed with hypertension. Out of the 20,908 records initially retrieved through this database identification,10 high-quality articles were selected and synthesized comprehensively. The results: A substantial body of clinical evidence indicates that various categories of antihypertensive agents possess highly specific and unique adverse effect profiles.The use of ACE inhibitors frequently induces a dry cough, CCBs prompt peripheral edema, diuretics disrupt electrolyte balance, whereas beta-blockers trigger fatigue and bradycardia. Furthermore, clinical complaints such as sleep disturbances and myalgia (muscle pain) have been identified as pivotal factors driving patients to neglect their treatment regimens. Statistical analysis confirms a significant correlation between the emergence of specific adverse effects and diminished medication adherence among hypertensive patients. Suggestions: The pharmacological class-based side effects of antihypertensive drugs significantly influence treatment adherence in hypertensive patients. Consequently, proactive clinical monitoring and intensive patient education are vital strategies to enhance adherence and ensure the success of hypertension management.